O turismólogo como agente social: limites e possibilidades - Csordas, Marisa (2009)
This dissertation aims to identify potential working opportunities for the graduated professionals in Tourism who intend to accomplish activities related with Social Sciences. The human focus specially given to this paper is due to the misjudged view taken by the society and by the touristic market itself that the graduated professionals in Tourism are prepared only to work in supportive, administrative or financial positions. This study evaluates currently curriculum offered at the Tourism graduation courses to check if these curriculum confer the necessary applied and social human skills to the Tourism professionals. Discussions on the curriculum adequacy are based on classical postulates from Sociology and Tourism, like Human Behavior in Work. The field methodology comprehended a comparative analysis between the curriculum of Tourism graduation courses offered by two renown Universities with different cultural and goal approaches. Also an inquiry was called from laymen and Tourism professionals and students already working in activities related to Social Sciences in order to compare their impressions and opinions about the Tourism usual duties and assignments. Data collected from the methodology applied above is a powerful instrument to know the real possibilities and Limits for the tourism´s professional work in social application areas